THE CYTOTOXIC AND ANTILEISHMANIAL EFFECTS OF SATUREJA KHUZESTANICA ESSENTIAL OIL - Farnaz Kheirandish; Rouzbeh Chegeni; Bahram Delfan; Mahboubeh Jabari; Farzad Ebrahimzadeh; Marzieh Rashidipour (Herbal Medicines Journal, 2017)
Background and Aim: Leishmaniasis is endemic in 98 countries including Iran. Pentavalent antimony compounds resistance as first-line therapy is increasing in some local areas. Also side effects of these drugs are limited at the beginning of treatment, but the toxicity increases with time. The aim of this study was to assess the effect of Satureja khuzestanica essential oil (SKEO) on promastigote and amastigote Leishmania major forms.